PENGARUH DIGITALISASI ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN SIKAP WAJIB PAJAK SEBAGAI VARIABEL MEDIASI (Studi Pada KPP Pratama Semarang Gayamsari) - Denia Mazaya Retsa Utomo; Herry Laksito (Diponegoro Journal of Accounting, 2026)
Taxpayer compliance is one of the main factors in the success of the tax system in Indonesia. Although various digital systems such as e-Filing, e-Billing, and DJP Online have been implemented, the level of compliance of individual taxpayers is still not optimal. This study aims to analyze the influence of digitization of tax administration on the compliance of individual taxpayers with taxpayer attitudes as a mediation variable.This study uses a survey method with the distribution of questionnaires to 100 individual taxpayers registered at KPP Pratama Semarang Gayamasari. The sampling technique was carried out by random sampling method, while the data analysis used multiple linear regression and mediation tests.Based on the results of this study, it is shown that the digitization of tax administration has a positive and significant effect on the compliance of individual taxpayers. Taxpayers' attitudes also have a positive effect and mediate the relationship between the digitization of tax administration and taxpayer compliance.